IL‐30 (IL27p28) attenuates liver fibrosis through inducing NKG2D‐rae1 interaction between NKT and activated hepatic stellate cells in mice - Mitra, Abhisek; Satelli, Arun; Yan, Jun; Xueqing, Xia; Gagea, Mihai; Hunter, Christopher A.; Mishra, Lopa; Li, Shulin (Hepatology (Baltimore, Md.), 2014)
Chronic hepatic diseases, such as cirrhosis, hepatocellular carcinoma, and virus‐mediated immunopathogenic infections, affect billions of people worldwide. These diseases commonly initiate with fibrosis. Owing to the various side effects of antifibrotic therapy and the difficulty of diagnosing asymptomatic patients, suitable medication remains a major concern. To overcome this drawback, the use of cytokine‐based sustained therapy might be a suitable alternative with minimal side effects. Here, we studied the therapeutic efficacy and potential mechanisms of interleukin (IL)−30 as antifibrosis therapy in murine liver fibrosis models. CCl4 or 3,5‐diethoxycarbonyl‐1,4‐dihydrocollidine (DDC) 0.1% (wt/wt) Purina 5015 Chow (LabDiet, St. Louis, MO) was fed for 3 weeks to induce liver fibrosis. Either control vector (pCtr) or pIL30 was injected hydrodynamically once per week. A significant decrease in collagen deposition and reduced expression of alpha‐smooth muscle actin (α‐SMA) protein indicated that IL‐30‐based gene therapy dramatically reduced bridging fibrosis that was induced by CCl4 or DDC. Immunophenotyping and knockout studies showed that IL‐30 recruits natural‐killer–like T (NKT) cells to the liver to remove activated hepatic stellate cells (HSCs) significantly and ameliorate liver fibrosis. Both flow cytometric and antibody‐mediated neutralization studies showed that liver NKT cells up‐regulate the natural killer group 2, member D (NKG2D) ligand and bind with the NKG2D ligand, retinoic acid early inducible 1 (Rae1), and positively activated HSCs to ameliorate liver fibrosis. Furthermore, adoptive transfer of liver NKT cells in T‐cell‐deficient mice showed reduction of fibrosis upon IL‐30 administration. Conclusions: Highly target‐specific liver NKT cells selectively remove activated HSCs through an NKG2D‐Rae1 interaction to ameliorate liver fibrosis after IL‐30 treatment. (Hepatology 2014;60:2026–2038)